On Animals: An extended review of David Clough’s two-volume work - Lesser, Ellen Grace (Studies in Christian ethics, 2021)
David Clough’s two-volume work On Animals claims to be the first systematic Christian theological reflection on the place of nonhuman animals within creation which also provides an ethical reflection on what that might mean for our relationship with nonhuman animals in contemporary (Western) society. In this extended review, we provide a summary of the cumulative arguments across both volumes of On Animals before offering our reflections. While we agree with many though not all of Clough’s theological conclusions, we ultimately conclude that Clough’s ethical solutions are too radical in places, and too optimistic without economic and systemic changes as to how humans relate to the nonhuman world.